Determination of phthalate acid esters (PAEs) in carbonated soft drinks with MSPE/GC–MS method. (2nd October 2018) - Moazzen, Mojtaba; Mahvi, Amir Hossein; Shariatifar, Nabi; Jahed Khaniki, Gholamreza; Nazmara, Shahrokh; Alimohammadi, Mahmood; Ahmadkhaniha, Reza; Rastkari, Noushin; Ahmadloo, Mahsa; Akbarzadeh, Arash; Dobaradaran, Sina; Norouzian Baghani, Abbas
Abstract: In this study, at first were prepared novel multi-walled carbon nanotubes modified with catalytic nanoparticles of iron oxide and silver (MWCNTs-Fe3 O4 /Ag) by mixing the magnetic particles. Due to their excellent absorption and desorption capability towards hydrophobic compounds, the magnetic MWCNTs were used as adsorbent of magnetic solid-phase extraction (MSPE) to extract phthalate acid esters (PAEs). Our results showed the highest concentration of phthalate esters of bis(2-ethylhexyl)phthalate (DEHP) which is much higher than the standard level in the four samples (6766.6, 9201, 9301.6, and 14, 008 ng/L). Finally, the established MSPE-GC/MS method was successfully applied to the determination of PAEs from carbonated soft drinks and the MSPE-GC/MS method developed in current study provides a new option for the detection of PAEs from carbonated soft drinks with complex matrices.